2020
DOI: 10.35848/1347-4065/ab9713
|View full text |Cite
|
Sign up to set email alerts
|

Degradation prediction using displacement damage dose method for AlInGaP solar cells by changing displacement threshold energy under irradiation with low-energy electrons

Abstract: Performance degradation prediction for space solar cells under irradiation with low-energy electrons is greatly affected by displacement threshold energy (Ed) when a displacement damage dose (DDD) model is used. According to recent studies, the Ed of P atoms is much lower than the conventional Ed value in InP-type solar cells irradiated with low-energy electrons. This indicates that the value of Ed typically used in DDD model leads to significant error in performance degradation prediction. In this study, degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…T d , for example, is an important quantity that can significantly affect the NIEL [185,186] and its accurate estimation can be accessed by AIMD simulations [187,188]. Recent results for T d in semiconductors have shown that the electronic excitations can, in general, reduce their value [122], in line with previous experimental results [189]. The effect of electronic excitations consists in weakening the atomic bonds making it easier to displace an atom from its equilibrium position.…”
Section: Improving the Model For Solar Cell Degradation Via A Multisc...supporting
confidence: 69%
“…T d , for example, is an important quantity that can significantly affect the NIEL [185,186] and its accurate estimation can be accessed by AIMD simulations [187,188]. Recent results for T d in semiconductors have shown that the electronic excitations can, in general, reduce their value [122], in line with previous experimental results [189]. The effect of electronic excitations consists in weakening the atomic bonds making it easier to displace an atom from its equilibrium position.…”
Section: Improving the Model For Solar Cell Degradation Via A Multisc...supporting
confidence: 69%
“…11) For this reason, a prediction model of performance degradation has been previously established. 12) Parameters such as the short-circuit current (J sc ), open-circuit voltage (V oc ), and maximum power (P max ) monotonically decrease as a function of proton 11) /electron 13) fluence. This tendency is explained by the radiation degradation model proposed in Ref.…”
mentioning
confidence: 99%